Central America Urbanization Review : Making Cities Work for Central America - World Bank Group (World Bank, Washington, DC, 2016)
Central America is undergoing an important transition, with urban populations increasingat accelerated speeds, bringing pressing challenges as well as opportunities to boost sustained,inclusive and resilient growth. Today, 59 percent of Central America's population lives in urban areas, but it is expected that within the next generation 7 out of 10 people will live in cities, equivalent to adding 700,000 new urban residents every year. At current rates of urbanization, the region’s urban population will double in size by 2050, welcoming over 25 million new urban dwellers, calling for better infrastructure, higher coverage and quality of urban services and greater employment opportunities. As larger numbers of people concentrate in urban areas, Central American governments at the national and local levels face both opportunities and challenges to ensure the prosperity of their country's present and future generations.